Fisetin Attenuates Myocardial Ischemia-Reperfusion Injury by Activating the Reperfusion Injury Salvage Kinase (RISK) Signaling Pathway - Shanmugam, Karthi; Boovarahan, Sri Rahavi; Prem, Priyanka; Sivakumar, Bhavana; Kurian, Gino A (Frontiers in Pharmacology, 2021)
Ischemia-reperfusion (I/R) injury is an unavoidable injury that occurs during revascularization procedures. In the previous study, we reported that fisetin is a natural flavonoid that attenuates I/R injury by suppressing mitochondrial oxidative stress and mitochondrial dysfunction. Though fisetin is reported as a GSK3β inhibitor, it remains unclear whether it attenuates myocardial ischemia by activating the phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) pathway, thereby inhibiting the downstream GSK3β, or by directly interacting with GSK3β while rendering its cardioprotection. In this study, the research team investigates the possible mechanism of action of fisetin while rendering its cardioprotective effect against myocardial I/R injury in rats. For this investigation, the team utilized two myocardial I/R models: Ligation of the left anterior descending artery and Langendorff isolated heart perfusion system. The latter has no neurohormonal influences. The PI3K inhibitor (Wortmannin, 0.015 mg/kg), GSK3β inhibitor (SB216763, 0.7 mg/kg), and fisetin (20 mg/kg) were administered intraperitoneally before inducing myocardial I/R. The result of this study reveals that the administration of fisetin decreases the myocardial infarct size, apoptosis, lactate dehydrogenase, and creatine kinase in serum\perfusate of the rat hearts subjected to I/R. However, the inhibition of PI3K with Wortmannin significantly reduced the cardioprotective effect of fisetin both in the ex vivo and vivo models. The administration of GSK3β inhibitor after the administration of fisetin and Wortmannin, re-establishing the cardioprotection, indicates the major role of PI3K in fisetin action. Changes in myocardial oxidative stress (level) and mitochondrial functional preservation of interfibrillar and subsarcolemmal mitochondria support the above findings. Hence, the team here reports that fisetin conferred its cardioprotection against I/R injury by activating the PI3K/Akt/GSK3β signaling pathway in rat hearts.